Necessary conditions for ECVET implementation - Le Mouillour, Isabelle [Verfasser] (Publications Office of the European Union, 2012)
"The European credit system for vocational education and training (ECVET) has benefited from the development of national qualifications frameworks and the learning outcomes approach to qualifications. It has also profited from the mutual trust and transparency created by successful learning mobility and lifelong learning experiences. The year 2012 is the first European milestone in the development of ECVET. It is an occasion to take stock - to invite the Member States to consider and discuss the conditions and measures needed for implementation of ECVET, the success of which depends on institutional, political, as well as cultural aspects of education and training systems in Europe. In this booklet, Cedefop, in consultation with other education and training stakeholders in Europe, presents 15 conditions and measures designed to promote a structured approach to implementation of ECVET, including a bigger role for peer learning." (Hrsg., BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Implementation; Europäische Union